Expression of PCNA, Ki-67 and COX-2 in breast cancer based on DCE-MRI image information. Issue 12 (December 2020) - Qiu, Xiaoming; Wang, Hong; Wang, Zhen; Fu, Yufei; Yin, Jianjun
Abstract: In order to explore the application value of DCE-MRI in clinical diagnosis and treatment, guide early clinical diagnosis, evaluate prognosis, guide clinical selection of treatment options and improve medical level, the expression of adenocarcinoma, its relationship with clinicopathology, and the significance of co-expression of the proliferating cell nuclear antigen (PCNA), Ki67 protein and cyclooxygenase 2 (COX-2) in breast cancer are analyzed. The results show that the positive expression rates of ki67, PCNA, and COX-2 in breast cancer patients are significantly higher than those in breast cancer patients (P < 0.05). Positive expressions of ki67, PCNA, and COX-2 in breast cancer patients are not correlated with age, tumor size and clinical stage (P > 0.05). There is no significant difference (P > 0.05) between the pathological types of breast cancer and positive expressions of ki67, PCNA and COX-2 in all the samples studied. Therefore, there is a correlation between DCE-MRI imaging features and prognostic indicators in breast cancer.